Representación de prácticas en aula a partir de instrumentos análogos y digitales en el desarrollo de ejercicios de Diseño (REVISTA NODO, 2024)
A summary of the process of representing classroom practices using analog and digital instruments in the development of design exercises is presented, applied to the architecture program at the Universidad Antonio Nariño in the city of Ibagué. This guide aims to contrast the Bruce Archer method, structured in three phases: analytical, creative, and executive, specifically applied to the Advanced Continuity Workshop G-4 at the Universidad Antonio Nariño, 2019. Through a descriptive analysis, it was revealed how each phase of the Archer method was integrated into the development of creative competencies of the students in the design exercises, addressing the use of both analog and digital tools. This process allowed for the contrast of their educational experience, demonstrating the effectiveness and applicability of both types of instruments during the semester. The results obtained were structurally supported, highlighting the importance of combining traditional and modern approaches in architectural education.
Keywords: design; experiences; tools; intruments; methodology